Carrie [videorecording (DVD)] : 2-pack. - De Palma, Brian; Monash, Paul, 1917-2003; Hirsch, Paul, 1945-; Peirce, Kimberly; Misher, Kevin; Percy, Lee; Spacek, Sissy; Travolta, John, 1954-; Laurie, Piper, 1932-2023; Moretz, Chloë, 1997-; Greer, Judy, 1975-; Doubleday, Portia; et al. (Twentieth Century Fox Home Entertainment, 2014)
Carrie: all hell breaks loose when a tortured, misfit teenager unleashes her secret telekinetic powers against her psychotic mother and sadistic classmates.